Causes and Consequences of Postponing the Decision to Marry in the Opinion of Young Adults - Rabenda-Nowak, Aleksandra; Wylęgły, Kamila (Journal of Education Culture and Society, 2022)
Aim. The aim of this article is to analyse why young adults in the postmodern world postpone the decision to marry. The authors want to present the reasons for this situation on the basis of surveys conducted with young adults aged 18-35 years old, taking into consideration both psychosocial and economic-cultural factors.Methods. In the research procedure, the authors used the survey method and the questionnaire interview technique. The unsupervised survey questionnaire was distributed to the respondents online. The research sample consisted of 28 persons in the age group of young adults. All the respondents were in informal partnerships.Results. Among young adults aged 18-35 years old, reasons for postponing marriage may be divided into psychosocial, related to the pressure of society to carry out developmental tasks and social roles; as well as economic and cultural, focusing on cultural changes and economic standards of young people.Conclusion. Young adults see the consequences of postponing the decision to marry, but it seems like changing cultural and social circumstances of the postmodern world allow them to make a conscious decision regarding their future. They have a neutral or positive attitude towards postponed marriage.